2013
DOI: 10.1016/j.mayocp.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Supplementation to Improve the Vitamin D Status of Breast-fed Infants: A Randomized Controlled Trial

Abstract: Objective To determine if a single monthly supplement was as effective as a daily maternal supplement in increasing breast milk vitamin D to achieve vitamin D sufficiency in their infants. Patients and Methods Forty mothers with exclusively breastfed infants were randomized to receive oral cholecalciferol (vitamin D3) 5000 IU/d for 28 days or 150,000 IU once. Maternal serum, breast milk, and urine were collected on days 0, 1, 3, 7, 14 and 28; infant serum was obtained on days 0 and 28. Enrollment occurred be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 37 publications
(44 reference statements)
6
94
0
3
Order By: Relevance
“…7,8,18 It is the parent compound, vitamin D itself, which overwhelmingly gets transferred into human milk from the maternal circulation. 8,17,22,52,53 7,8,19,52 This fact is precisely why the AAP recommends every nursing infant receive a daily supplement of 400 IU vitamin D. 11 However, this last recommendation treats only the infant and does not address the core problem of why breast milk has such low concentrations of vitamin D. Also, the AAP recommendation 11 is rarely followed as evidenced by our baseline entry data for breastfed infants (Table 1). In our study infants, only 12% were being given supplements at baseline, which concurs with previous reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,18 It is the parent compound, vitamin D itself, which overwhelmingly gets transferred into human milk from the maternal circulation. 8,17,22,52,53 7,8,19,52 This fact is precisely why the AAP recommends every nursing infant receive a daily supplement of 400 IU vitamin D. 11 However, this last recommendation treats only the infant and does not address the core problem of why breast milk has such low concentrations of vitamin D. Also, the AAP recommendation 11 is rarely followed as evidenced by our baseline entry data for breastfed infants (Table 1). In our study infants, only 12% were being given supplements at baseline, which concurs with previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…1,3,11 Over the decades, we and others have reported the vitamin D content of human milk and thus its antirachitic activity. 8,22,28,[50][51][52] These studies have provided valuable information. Universally, the antirachitic activity of human milk is quite low, 5 to 80 IU/L, unless the lactating mother is ingesting a significant amount of vitamin D daily or getting significant total body UV exposure.…”
Section: Resultsmentioning
confidence: 99%
“…A dose of 6,400 IU/day raises the milk vitamin D content sufficiently so that the babies achieved 25OHD values of 115 nM (46 ng/ml), the same level reached by babies who received 300 IU of vitamin D directly in the form of oral drops (965). A daily maternal dose of 5,000 IU/day raised maternal 25OHD to 400 nM (160 ng/ml) and neonatal 250HD to 98 nM (39 ng/ml), while a single maternal dose of 150,000 IU had a similar effect (672).…”
Section: Human Datamentioning
confidence: 63%
“…Observational cohort studies (145,731,862,893) and randomized interventional trials (13,14,60,402,453,672,780,788,789,965) have not shown any effect of higher 25OHD concentrations or vitamin D supplementation to alter maternal mineral or skeletal homeostasis in otherwise healthy, lactating women across a broad range of vitamin D intakes and 25OHD levels. Vitamin D supplementation raises maternal 25OHD levels with a similar dose-response effect as in nonpregnant or nonlactating women.…”
Section: Human Datamentioning
confidence: 99%
See 1 more Smart Citation